Bio-nanocomposite Films Reinforced with Various Types of Cellulose Nanocrystals Isolated from Oil Palm Biomass Waste - Junidah, Lamaming; Rokiah, Hashim; Leh, Cheu Peng; Othman, Sulaiman; Sofie Zarina, Lamaming (Springer Nature, 2020)
Studies of bio-nanocomposites using sustainable green materials from biomass waste are presently gain the attention worldwide. This study investigated the properties of bio-nanocomposite flms from polyvinyl alcohol incorporated with 1%, 3%, and 5% via solvent casting method using various types of oil palm trunk cellulose nanocrystals isolated using various types of treatment. The produced bio-nanocomposite flms were characterized for their mechanical behavior, morphological properties, thermal properties, and functionality groups and the efect of adding the oil palm trunk cellulose nanocrystals into the bio-nanocomposites flms were then evaluated. The results showed that the mechanical properties and thermal stabilities of the bio-nanocomposite flms increased with the incorporation of cellulose nanocrystals. The bio-nanocomposite flms added with 3% cellulose nanocrystals with pre-hydrolysis treatment showed better mechanical and thermal properties and hence have a great potential to be utilized as a raw material or reinforcement in the packaging industries.